Invited Editorial: Why Micro-Foundations for Resource-Based Theory Are Needed and What They May Look Like - Foss, Nicolai J. (Journal of Management, 2011)
One of the important events in the development of resource-based theory (RBT) over the past decade has been the call for establishing micro-foundations for RBT. However, the micro-foundations project is still largely an unfulfilled promise. This article clarifies the nature of the micro-foundations project, discusses what it may add in terms of additional explanatory leverage, and specifically addresses micro-foundations in the context of knowledge-based value creation, a key theme in RBT.